2016
DOI: 10.4028/www.scientific.net/msf.861.201
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nano-TiO<sub>2</sub> Additive Oil-in-Water Lubricant for Hot Steel Rolling

Abstract: To obtain a low cost, environmentally friendly and effective lubricant, a novel nanoTiO2 additive oil-in-water (O/W) lubricant for hot steel rolling has been developed. Based on the contact angle, tribological and hot rolling tests, the performance of the nanoTiO2 additive O/W lubricants was evaluated and discussed. The results show that the strongest adhesion force between the nanoTiO2 additive O/W lubricant and the work roll is obtained after addition of 4% nanoTiO2 additive in the 1% O/W lubricant. The nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…They include two-dimensional materials ( e.g., graphene, hexagonal boron nitride (h-BN), MoS 2 , WS 2 ...), nanoparticles ( e.g. , Cu, Ni, TiO 2 , ZrO 2 , SiO 2 , CaCO 3 ...), organic oiliness friction modifiers and wear-resistant additives for engine conditions, , and inorganic polymer glasses (borate, silicate, phosphate, borosilicate...) for elevated temperature conditions. Under sliding conditions at mixed and particularly boundary regimes, these solid lubricants experience thermally induced chemical reactions, adsorption, and diffusion onto the sliding surfaces. , In addition, the stress-shearing not only induces flash temperature but also provides the intermixing effect that organizes and constructs the formation of complex hierarchical layers. These hierarchical layers, well known as “tribofilm”, have a number of particular properties that either separate the direct contact between the asperities or deliver the low shearing capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…They include two-dimensional materials ( e.g., graphene, hexagonal boron nitride (h-BN), MoS 2 , WS 2 ...), nanoparticles ( e.g. , Cu, Ni, TiO 2 , ZrO 2 , SiO 2 , CaCO 3 ...), organic oiliness friction modifiers and wear-resistant additives for engine conditions, , and inorganic polymer glasses (borate, silicate, phosphate, borosilicate...) for elevated temperature conditions. Under sliding conditions at mixed and particularly boundary regimes, these solid lubricants experience thermally induced chemical reactions, adsorption, and diffusion onto the sliding surfaces. , In addition, the stress-shearing not only induces flash temperature but also provides the intermixing effect that organizes and constructs the formation of complex hierarchical layers. These hierarchical layers, well known as “tribofilm”, have a number of particular properties that either separate the direct contact between the asperities or deliver the low shearing capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed that nanoparticles have potential applications in the steel rolling process [ 10 , 11 ], machine cutting process [ 12 , 13 , 14 ], micro-drilling process [ 15 ], etc. Previous studies reported that nano-TiO 2 has good friction-reducing, anti-wear, and cooling properties, so it can reduce the coefficient of friction and rolling force during the hot rolling process [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%